PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN SEVERITY INKLUSI BAHAN BAKU BAJA DENGAN MENGGUNAKAN LOGIKA FUZZY MAMDANI - Riki Ridwan Margana; Yani Iriani; Imtiyaz Imtiyaz (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Steel is one of the raw materials used by PT. XYZ in the manufacture of its defense products; therefore, quality control (QC) and checking process become the most essential part in the process. To ensure that the steel raw materials used reach the standards, metallurgical properties are examined using several criteria must be carried out well, as microstructure, grain size, decarburization and impurities (inclusions). Inclusions or impurities are unwanted non-metal compounds and are the main factor for the initial appearance of ductile fracture and brittle facture during the production process. The severity of the inclusions in steel raw materials affects the next process so that errors in readings to determine the severity of minor or major inclusions must be minimized. This is because when the inclusion severity level that read is included in the major level then the steel raw material cannot be used and turns to be scrap and causes losses to the company. To minimize the matters, operator accuracy is required in analyzing by a comparison table, because this method analyzes the inclusion compounds one by one and it takes ± 1 minute to determine the severity. The purpose of this research is to build a quality decision-making system based on fuzzy mamdani logic that is used to determine the severity of inclusions and to compare the results of system processing with operators to see the accuracy of the system and time efficiency that has been built. In this study using the Mamdani fuzzy logic method with the variables used are Alumina inclusion length, Silicate inclusion length, Alumina inclusion width and Silicate inclusion width. The system is built using matlab software. The system test results from the 6 samples used to obtain comparisons according to the operator and the system are stated to be minor, making the accuracy obtained quite good and in terms of time, the determination process with the system takes less time, namely ± 2 seconds